First touch: An immediate response to surface recognition in conidia of Blumeria graminis - Nielsen, K.; Nicholson, R.; Carver, T.; Kunoh, H.; Oliver, Richard (2000)
Conidia of the plant pathogen Blumeria graminis recognize and respond to features of certain substrata. Appropriate surfaces induce release of an extracellular proteinaceous matrix from the body of the conidium. Contact with a hydrophobic substratum elicits almost immediate release of the matrix at the contact interface. In this investigation we present, for the first time, evidence that recognition of the substratum by conidia can stimulate uptake of anionic, low-molecular-weight materials before germination. This facilitated transport could be a mechanism for recognition of the host and determination of the direction of growth of the emerging germ tube toward the host leaf surface.